P203 Development Of An Optimal F/hn Pseudotyped Siv Vector For Cf Gene Therapy. (10th November 2014) - Hyde, SC; Alton, Ewfw; Boyd, AC; Connolly, MM; Chan, M; Davies, JC; Davies, LA; Gea-Sorli, S; Griesenbach, U; Hasegawa, M; Innes, JA; Inoue, M; et al.
Abstract : We are developing lung gene transfer vectors to treat acquired and inherited lung disorders such as cystic fibrosis, and have identified two platforms for efficient respiratory gene delivery: one non-viral system based on CpG-free plasmid DNA combined with cationic lipids (pDNA/GL67A), which has recently completed evaluation in a Phase IIb clinical study; and one novel viral system based on a recombinant simian immunodeficiency virus pseudotyped with the F/HN proteins of Sendai virus (rSIV. F/HN) to promote airway cell uptake. Here we report on the development of a "third generation" rSIV. F/HN vector suitable for use in the clinic. The vector is manufactured by transient transfection of cultured human cells using five producer plasmids, all of which have been engineered to be pharmacopoeia compliant. A variety of vector configurations, including a range of enhancers/promoters and transgenes, were evaluated in a panel of airway models. rSIV. F/HN vectors directed high-level, robust gene expression in fully differentiated human airway cells, human nasal brushings and human and sheep lung slices. In the mouse nose and lung, the preferred configuration directed up to x500-fold higher transgene expression than the non-viral platform, for the lifetime of the animal. Transgene expression was observed in 14.1% of lung epithelial cells (p < 0.0001 compared to controls). Repeated monthly administration (3X) was possible without loss of expression or significant histological inflammatory reactivity. Reassuringly, insertion site profiling from transduced cell lines and mouse nose/lung samples reveals a pattern of integration comparable to those reported for other lentiviral vectors in clinical development, with no evidence for enrichment of insertion at undesirable loci. The stability of rSIV. F/HN vectors was evaluated in two bronchoscope catheters and two aerosol generation devices. Encouragingly for clinical translation, no significant loss of transduction activity was noted with any of these clinically relevant delivery devices (p = 0.64). Delivery of rSIV. F/HN expressing CFTR to sheep lung resulted in CFTR mRNA at ∼30% the levels of endogenous ovine CFTR (p < 0.0001 compared to non-treated lobes), exceeding presumed therapeutic levels. With the majority of translational hurdles addressed, we are now entering toxicology studies and the final stages of pharmaceutical development prior to entering clinical trials.